Research Progress of Absorption Refrigeration Working Pairs - Bian Yifeng; He Guogeng; Cai Dehua; Xiao Ruxi; Zhang Aoni (Zhileng xuebao)
The development of absorption refrigeration has attracted people’s attention under the theme of energy conservation and environmental protection. As one of the core techniques, the development of absorption refrigeration working pairs plays an important role. Some hot topics in the field of absorption refrigeration were enumerated and the gap between theoretical research and practical application problems were pointed out. According to the differences of refrigeration, there are five groups of working pairs, such as ammonia, water, alcohol, fluoride, etc. Historical and current situation of the five-group working pairs were reviewed and defects of the traditional ones were analyzed. This paper explored the relevant optimization measures, new working pairs and compared their performance with that of the traditional ones. In addition, the current research situation of NH3-NaSCN and NH3- LiNO3 was emphasized and a comparison between their advantages and disadvantages in different conditions was made. Moreover, different kinds of salt combinations were introduced to replace LiBr and weaken the corrosivity of LiBr-H2O. On the basis of current researches, more works should be done on the improvement of existing working pairs’ performance and exploration of new ones.